2016
DOI: 10.1038/srep36962
|View full text |Cite
|
Sign up to set email alerts
|

Soluble γc cytokine receptor suppresses IL-15 signaling and impairs iNKT cell development in the thymus

Abstract: The soluble γc protein (sγc) is a naturally occurring splice isoform of the γc cytokine receptor that is produced by activated T cells and inhibits γc cytokine signaling. Here we show that sγc expression is also highly upregulated in immature CD4+CD8+ thymocytes but then downregulated in mature thymocytes. These results indicate a developmentally controlled mechanism for sγc expression and suggest a potential role for sγc in regulating T cell development in the thymus. Indeed, sγc overexpression resulted in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 57 publications
5
21
0
Order By: Relevance
“…sγc has previously been shown to skew CD4 + T cells to Th17 by dampening IL‐2 signals and suppress NKT cell development by downregulating of IL‐15 signals . Here, we have confirmed these previous study findings, and went a step further by showing that sγc deficiency could augment IFNγ, TNFα and ganzyme B expressions of activated CD8 + T cells.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…sγc has previously been shown to skew CD4 + T cells to Th17 by dampening IL‐2 signals and suppress NKT cell development by downregulating of IL‐15 signals . Here, we have confirmed these previous study findings, and went a step further by showing that sγc deficiency could augment IFNγ, TNFα and ganzyme B expressions of activated CD8 + T cells.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, we found that sγc directly interacts with membrane IL‐2 receptors and interfere with ligand/receptor interaction. Altogether with current study and our previous reports, we propose that sγc produced upon TCR stimulation competes with mγc to bind IL‐2Rβ and opposes formation of signaling competent heterotrimeric IL‐2/IL‐2Rβ/mγc complexes. In fact, recent reports using immunofluorescence co‐patching and FRET analysis documented that mγc and IL‐2Rβ already can form 1:1 heterodimeric complexes even in the absence of IL‐2 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations